Comparación de tres sistemas de labranza en maíz (1978)
An experiment was conducted at the Montelindo form, of the Universidad de Caldas (Colombia) with an altitude of 1.050 m. Above sea level. The objetives of the experiment were: To analize and compare the behavior of corn (Zea mays) under three different tillage systems, and to determine the effect of them on some of the physical properties of the soil. The main results obtained show that the reduction in the number of tillage operations do not substantially affect neither the development of the crop nor its production. Some of the soil physical properties such an soil moisture content and the apparent specific gravity are more stable when the number of tillage operations is reduced.